Analisis Hukum Tentang Isbat Nikah Menurut KUH Perdata dan KHI Indonesia - -, Rita Khairani; Bawono, Royan (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2022)
This study examines the legal analysis of marriage isbat according to the Civil Code, Law Number 1 of 1974 concerning Marriage and the Indonesian KHI. Based on the results of the study, it was found that marriage isbat is regulated in the Civil Code Articles 100-102. Regarding marriage isbat, the Civil Code does not provide strict limits on the elements that can be considered by the judge in determining the validity of a marriage. However, it has weaknesses, namely the disparity between the Indigenous, foreign and Chinese residents, this is what causes the absence of unification of a regulation and is the background for the birth of Law Number 1 of 1974 concerning Marriage. Law Number 1 of 1974 concerning Marriage also does not provide limitations regarding marriage events that can be requested for ratification. In contrast to the two provisions, the Compilation of Islamic Law (KHI) regulates the isbat of marriage in a strict manner by providing limitations as described in Article 7 paragraphs (1) to (4) in which a marriage can only be proven by a Marriage Certificate. A marriage cannot be proven by a marriage certificate, its marriage certificate can be submitted to the Religious Court/Syar'iyyah Court. The marriage isbat submitted is limited to five things and those who are entitled to apply for itsbat marriage are husband or wife, their children, marriage guardians and parties with an interest in the marriage.